Quantitative comparison of CSVD imaging markers between patients with possible amyloid small vessel disease and with non-amyloid small vessel disease - Chun-Qiang Lu; Ying Liu; Jia-Rong Huang; Meng-Shuang Li; Yan-Shuang Wang; Yan Gu; Di Chang (NeuroImage: Clinical, 2024)
The spatial distribution patterns of cerebral microbleeds are associated with different types of cerebral small vessel disease (CSVD). This study aims to examine the disparities in brain imaging markers of CSVD among patients diagnosed with possible amyloid and non-amyloid small vessel disease. The head MR scans including susceptibility-weighted imaging (SWI) sequences from 351 patients at our institute were collected for analysis. CSVD imaging markers were quantified or graded across various CSVD dimensions in the patient images. Patients were categorized into the cerebral amyloid angiopathy group (CAA), hypertensive arteriopathy group (HA), or mixed small vessel disease group (Mixed), based on the spatial distribution of microbleeds. White matter lesions (WML) were segmented using an artificial neural network and assessed via a voxel-wise approach. Significant differences were observed among the three groups in several indices: microbleed count, lacune count at the centrum semiovale and basal ganglia levels, grade of enlarged perivascular space (EPVS) at the basal ganglia, and white matter lesion volume. These indices were substantially higher in the Mixed group compared to the other groups. Additionally, the incidences of cerebral hemorrhages (χ2 = 7.659, P = 0.006) and recent small subcortical infarcts (χ2 = 4.660, P = 0.031) were significantly more frequent in the HA group than in the CAA group. These results indicate that mixed spatial distribution patterns of microbleeds demonstrated the highest burden of cerebral small vessel disease. Microbleeds located in the deep brain regions were associated with a higher incidence of recent small subcortical infarcts and cerebral hemorrhages compared to those in the cortical areas.